Peace Negotiation in International Relations. - Wakkumbura, Menik (Department of International Relations. University of Colombo Press., 2020)
The book titled Peace Negotiation in International Relations is authored by Menik Wakkumbura. The book briefly examines the origin, development, characteristics & techniques of peace negotiation. This book contains four chapters–the first two chapters focus on evolvement and definition of peace negotiation in the field of conflict resolution. The third chapter examines the third-party role in peace processes as one of the vital peacemaking attempts. The case studies discussed are referred to peace processes in the Middle East, Africa, and Asia. The fourth chapter focuses on Norway’s role in peacemaking and peacebuilding with reference to Norwegian peacemaking efforts in the Middle East and particularly discussing Sri Lanka’s peace process (2002-2006).
Keywords: Peace Negotiation in International Relations